THE INFLUENCE OF SOIL TEXTURE AND ORGANIC MATTER ON THE RETENTION CURVES AT SOIL MOISTURE IN THE HUMIC CALCARIC REGOSOL OF THE OVCHE POLE REGION, NORTH MACEDONIA - Mile MARKOSKI, Tatjana MITKOVA , Vjekoslav TANASKOVIK , Stojanče NECHKOVSKI and Velibor SPALEVIC (Agriculture & Forestry, Vol. 66 Issue 2: 33-44, 2020, 2020)
This paper is a result of field and laboratory research of the soils (Rendzina Calcaric Regosol) in Ovche Pole region in the Republic of North Macedonia. The field research of the soils has been done according to methods described by Mitrikeski & Mitkova (2013). In laboratory, the following analyses have been carried with the soil samples: hygroscopic moisture, mechanical composition (soil texture), pH value of the soil solution, humus content and content of carbonates. The soil texture and chemical properties of the soils have been determined by standard methods described by Mitrikeski & Mitkova (2013). The soil moisture retention at pressures of 0.33, 6.25 and 15 bars was determined by bar extractor (Townend, et al., 2001; ICARDA 2001; Marinčić, 1971). The average content of physical sand and clay fractions was 59.50% and 40.50% respectively. The average content of individual soil separates is: coarse sand 20.85%, fine sand 38.65%, silt 18,29% and clay 22.21%. The content of humus in horizon Ap ranges from 1.87 to 2.2 with an average of 2.1% and this percentage decreases with depth in all examined profiles. In horizon Amo is 1.36%, in AC horizon 0.89% and the smallest is in parent material C, 0.69%. The moisture content of the soil at 0.33 bar is high in all horizons. The highest retention has horizon Amo 31.25% (higher content of humus and clay). The horizons AC, Ap and the parent material C have similar values (26.74%, 26.72 and 24.51%). The wilting point is not high (average 15.71% in Amo horizon). The results suggested a positive correlation in horizon Amo between the moisture retention at 0.33 and 15.00 bars and the content of physical clay and clay, as well as high negative correlation between the moisture retention at 0.33 and 15.00 bars and the content of sand. The retention curves in all horizons are almost horizontal at 2 bars in all the studied cases. The greatest decline of the retention curves occurs at lower pressures (< 1 bar). Gradual changes in the retention forces can be noticed coming with the change of moisture without jumps. This shows that the division of the soil moisture in different forms cannot be justified with the retention curve because the decrease of the amount of water does not have big jumps under different tensions.
Keywords: Rendzina Calcaric Regosol, texture soil, humus content, retention curves